Pengaruh Manajemen Kurikulum dan Profesionalisme Guru terhadap Mutu Pendidikan Pondok Pesantren Qotrun Nada Kota Depok Tahun 2019-2020 - Siti Syuaibah; Qowaid Qowaid; Efrita Norman (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2020)
Curriculum management and teacher professionalism are an important part of educational components in improving the quality of education. The order to achieve a good education and quality it is necessary to a good management, especially in the area of ​​curriculum that will be taught to students about the objectives, content or materials, implementation and evaluation of curricula. In addition to curriculum management there is also a need for professional educators to get students the best service from their teachers. This research inted to (1) Know the impact of curriculum management on the educational quality of Qotrun Nada islamic boarding school Depok, (2) Know the impact of teacher professionalism on the quality of education at Qotrun islamic boarding school Depok, (3) Know the impact of curriculum management and teacher professionalism on quality education Qotrun Nada islamic boarding school Depok. In this research the researcher uses quantitative descriptive with type of correlative research. The data were collected through a questionnaire from a population of 150 who were all teachers at the Qotrun Nada boarding school. Based on the analysis of the research data, the: Management of curriculum boarding, teacher professionalism and quality of education at Qotrun Tada boarding school Depok is good. Simultaneous boarding curriculum management and teacher professionalism influence the quality of education at Qotrun Nada boarding school. This is evidenced by the multiple linear regression equation model with a significance value of 0.000 <0.05, Ho rejected and Ha accepted. Keywords: Curriculum Management, Teacher Professionalism, and Educational Quality.